The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1177/0273475311430805
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Personal Selling Ethics Evaluations

Abstract: Sales career opportunities are growing, and the number of women in sales is increasing. Educators must adequately prepare both men and women for today's ethical sales dilemmas. Using the Personal Selling Ethics Scale, the current study analyzes the impact of idealism and relativism on the sales ethics evaluations of men and women. Results indicate that women evaluate sales ethics scenarios as less ethical than males and that varying positions on these ethical frameworks partially explain the divergence. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 55 publications
0
8
1
Order By: Relevance
“…In many arenas, variant educational approaches have been suggested in light of gender disparities. However, unlike sales ethics or sales negotiations in which substantive gender divergence may warrant gender-specific instruction (Donoho et al, 2012;Stevens & Whelan, 2019), the current study's findings suggest that gender-specific instruction is not required in sales technology.…”
Section: Discussioncontrasting
confidence: 53%
“…In many arenas, variant educational approaches have been suggested in light of gender disparities. However, unlike sales ethics or sales negotiations in which substantive gender divergence may warrant gender-specific instruction (Donoho et al, 2012;Stevens & Whelan, 2019), the current study's findings suggest that gender-specific instruction is not required in sales technology.…”
Section: Discussioncontrasting
confidence: 53%
“…Mirroring prior studies (Donoho, Heinze, & Kondo, 2012), the current study illustrates the strong need for sales ethics training. The overall mean PSE-2 score was 3.36, indicating an average student response between "somewhat unethical" and "neither unethical nor ethical."…”
Section: Implications For Sales Ethics Educationmentioning
confidence: 63%
“…For example, idealistic individuals were found to be more sensitive to ethical misconduct in sales, and relativistic individuals were found to be less sensitive. Likewise, Donoho, Heinze, and Kondo (2012) found that higher moral idealism scores resulted in critical ethical evaluations of sales ethics abuses, while higher relativism scores resulted in ethical evaluations that were less critical.…”
Section: Ethical Framework-moral Idealism and Moral Relativismmentioning
confidence: 98%
See 2 more Smart Citations